2018
DOI: 10.1002/nau.23473
|View full text |Cite
|
Sign up to set email alerts
|

Medication use and association with urinary incontinence in women: Data from the Norwegian Prescription Database and the HUNT study

Abstract: The odds for having UI were found to be about 1.5-fold in women using SSRIs and almost threefold in women using lamotrigine. The association with lamotrigine has not been reported previously, and should be further evaluated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…The association between the use of psychotropics and UI has previously been investigated in the same data material from HUNT3, and the selection of drugs in our model were chosen partly based on the results in this study [ 16 ]. Mauseth et al found adjusted associations between use of SSRIs and UI and between use of lamotrigine and UI, with ORs 1.52 and 2.73, respectively, for two or more prescriptions during the last 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The association between the use of psychotropics and UI has previously been investigated in the same data material from HUNT3, and the selection of drugs in our model were chosen partly based on the results in this study [ 16 ]. Mauseth et al found adjusted associations between use of SSRIs and UI and between use of lamotrigine and UI, with ORs 1.52 and 2.73, respectively, for two or more prescriptions during the last 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…The following drug groups were used in the analyses: Opioid analgesics (ATC-code: N02A), other analgesics (N02B), antiepileptic drugs (N03), lamotrigine (N03A X09), antiparkinson drugs (N04), antipsychotics (N05A), anxiolytics (N05B), hypnotics and sedatives (N05c), antidepressants (N06A) and selective serotonine reuptake inhibitors (SSRIs) (N06AB), urologics (G04BD), estrogens (G03C) and progesterons and estrogens in combination (G03F). We selected drug groups due to literature indicating possible association with UI [ 13 16 , 26 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most problematic would be documentation of actual prescription filling, but this is a topic of increasing interest to the medical and academic communities and access to such information we hope will improve. [32][33][34]…”
Section: Limitationsmentioning
confidence: 99%